Domestic Violence and Children Emotional Wellbeing in Kabale District: A Case Study of Rubaya Sub-County. - Kakuru, Mackson (Kabale University, 2024)
The study was about the effects of domestic violence on children's emotional wellbeing in the Rubaya sub-county Kabale District. The study was guided by objectives like identifying the forms and causes of domestic violence against children, establishing the impact of domestic violence on the emotional well-being of children, and examining the strategies of domestic violence in Rubaya Sub County in Kabale District. The study sampled 165 respondents out of 238 as the target population. A descriptive design was used in the study. The researcher used both Primary and secondary data. Secondary data was collected from documents and policies. Literature was reviewed using secondary data sources including other reports. journals. internet. research projects and information from the University library. The study also found that abused male children typically learn to be victimizers. You get beaten up when you're small; then when you're big. you repeat what you learned, and respondents gave their opinions that social isolation is also a factor in abuse. Respondents revealed that domestic violence leads to injuries, and women who experience intimate partner violence report an injury as a consequence of this, from the questionnaires, respondents mentioned that leads to unintended pregnancies, and induced abortions. and some respondents feel the need to increase efforts to raise massive social awareness of the criminal nature of domestic violence and the services available to victims. This should be done in the form of seminars, workshops, and massive sensitization over both traditional and social media platforms such as radios, and televisions. Facebook, YouTube, and other media platforms, the study concludes that domestic abuse cannot be blamed on drugs or alcohol consumption. Some perpetrators may have been drinking or taking drugs when they were abusive, but many have not. The study concludes that much like drugs and alcohol, stress is not a cause of domestic abuse. Abuse is a choice, intended to gain power and control over the victim. Generally, perpetrators of domestic abuse, regardless of how stressed they are. can limit their abusive behavior to their chosen victim/s. The study recommends that there is a need for empowerment directed at vulnerable and socially excluded domestic violence survivors is ideal as it might help women gain control of their lives and instill in them motivation to reclaim their position in the community. Empowerment intervention usually equips the individual with an instrument of self¬determination, provides competency awareness, and strengthens self-esteem.